Case report: Prompt response to radiotherapy and chemotherapy combined with crizotinib in gingival sarcomatoid squamous cell carcinoma with MET 14 mutation - Sun, Zhenhua; Xia, Bingjie; Zhang, Ming; Xu, Shuai; Ma, Yingqian; Zhang, Xianbo (Frontiers in Oncology, 2022)
Background: As a kind of squamous cell carcinoma of Head and Neck (HNSCC), gingival sarcomatoid squamous cell carcinoma (GSSCC) is a rare biphasic malignant neoplasm. To date, surgical resection was often utilized for gingival squamous cell carcinoma (GSCC), while for patients with advanced gingival carcinoma who cannot tolerate surgery, radiotherapy and chemotherapy can be regarded as a treatment strategy. Many molecular-targeted drugs were investigated and approved for the treatment of malignant diseases, including hematologic diseases and solid tumors. Although targeted therapies such as EGFR inhibitors have shown therapeutic efficacy in HNSCC, there are still some patients who cannot benefit from it. New therapeutic targets and strategies should be further explored. Case Presentation: An 83-year-old female was referred to our hospital with left lower gingival mass for more than 1 month in June 2021. Pathologic diagnosis is sarcomatoid squamous cell carcinoma. Due to the large tumor at the time of diagnosis and poor quality of life, the patient was intolerate to surgery, so she was given radiotherapy (RT) combined with concurrent chemotherapy (CT) with albumin bound paclitaxel. According to Next-generation sequencing (NGS) results (MET exon 14 skipping mutation-positive), She was treated with crizotinib, a tyrosine kinase inhibitor that targets MET. Through the comprehensive treatment, Patient’s condition promptly improved, clinical complete remission (CR) was achieved in 2 months, and obtained 9-month progression-free survival (PFS). She finally died from non-cancer-related diseases. Conclusion: Here we report the treatment of a GSSCC patient with MET mutation, who responded to crizotinib promptly and positively. It provides a new reference for understanding MET abnormalities in GSSCC, and offers a new idea for the targeted treatment of gingival carcinoma.